THE EFFECT OF LEVERAGE, THIN CAPITALIZATION, AND TAX HAVENS ON TAX AVOIDANCE WITH FIRM SIZE AS A MODERATING VARIABLE - Fahmi, Muhammad; Yanti, Harti Budi (JURNAL AKUNTANSI DAN AUDITING, 2024)
This study aims to analyze the effect of leverage, thin capitalization, and tax havens on tax avoidance, with firm size as a moderating variable in energy sector companies listed on the Indonesia Stock Exchange. The sample consists of energy sector companies listed on the Indonesia Stock Exchange (www.idx.co.id) for the years 2021 to 2023, resulting in a final sample of 204 observations 87 companies selected using a purposive sampling technique. Data was analyzed using SPSS software with multiple regression analysis, descriptive statistics, classical assumption tests, and hypothesis testing that the research results are Leverage and Thin Capitalization both have a moderately positive and statistically significant correlation with tax avoidance Tax Havens shows a weak and non-significant effect on Tax Avoidance Leverage and thin capitalization both have a moderate and statistically significant influence on tax avoidance Tax Havens, which moderate firm size, have a marginally significant but limited influence on tax avoidance.